CEREBELLAR DIFFUSE LARGE B CELL LYMPHOMA IN IMMUNOCOMPETENT FEMALE PATIENT - GA Sansoni; MLM Nucci; NC Oliveira; RD Portugal (Hematology, Transfusion and Cell Therapy, 2021)
Background: Diffuse large B cell lymphoma (DLBL) is the most common type of lymphoma worldwide, representing about 25% of all non-Hodgkin lymphomas. Among these lymphomas, primary DLBL of the central nervous system (CNS) is a rare category listed at 2016 revision of the World Health Organization classication of lymphoid neoplasms. First line treatment is based on methotrexate (MTX), with studies showing complete remission rates of 30 to 60% in patients who receive high-dose MTX, alone or in combination with other agents. The rarity of primary CNS lymphomas makes randomized trials dicult to do, but regimens usually include MTX plus one of the following drugs: cytarabine, procarbazine, temozolomide or rituximab in CD20 positive tumors. Aims: to present a case of primary CNS lymphoma presenting as multiple lesions in the cerebellum. Case presentation: We present a case of a 57-year-old female patient, without comorbidities or HIV seropositivity, diagnosed with diffuse large B cell lymphoma with cerebellar origin. During a period of 4 months the patient presented progressive difficulties to accomplish everyday activities quickly evolved, and were accompanied by aphasia, dysarthria, lack of motor coordination, nausea and vomiting. Her handwriting was unintelligible. A brain MRI showed enhanced leptomeningeal area associated with middle cerebellar peduncle lesions on both sides. Biopsy confirmed the diagnosis of lymphoma with immunohistochemistry showing positivity for CD20 and 40% Ki67. Bone marrow biopsy was normal and the serology for HIV, Epistein-Barr virus and hepatitis B and C viruses were negative. She was treated high dose induction immunochemotherapy with methotrexate (four doses of 3.5 g/m2), cytarabine (two cycles of 2 g/m2, twice a day for 2 days) and rituximab (four doses of 375 mg/m2). After the first cycle, the patient developed foreign accent syndrome (FAS) changing from her Brazilian accent to a Portuguese accent (within the same language). Despite FAS, other neurological symptoms ameliorated and the patient can once again write with her normal handwriting, have conversations and read. She was referred to complementary whole-brain radiotherapy. Discussion: Literature on cerebellar primary central nervous system lymphoma is scarce.1 A review of PCNSL reported only 9% of tumors with cerebellar involvement. The addition of high-dose cytarabine to high-dose methotrexate seems to be associated with improved response in patients with primary CNS lymphoma. However, cerebellar toxicity is a dose-dependent adverse effect of cytarabine and a concern in cases with previous cerebellar syndrome. FAS may be related to involvement of ’linguistic cerebellum’2 but apparently not associated with cytarabine. We showed that this combination was possible, without major neurologic events. Conclusion: Early diagnosis and treatment is important for the successful management of this aggressive and uncommon cerebellar tumor. Symptomatic improvement was fast after MTX initiation and the addition of cytarabine is feasible.